#TITLE_ALTERNATIVE# - PAHLEVI (NIM 12104086), REZA
Modeling and calculation of mineral reserves is a important matter in the process of mining. Modeling and calculation of mineral reserves is used as the basis for evaluating the decision whether a depositi is feasible or not to be mined. Modeling of mineral deposit is always expected as close as real situation. Therefore, the valuation and the necessary approaches to the methods so that a particular model can be made close to actual conditions. One type of model can be made based on the vertical section to interpolate the area among location. Drilling information should be analyzed based on several parameters so that the correlation can be made close to the actual conditions. There are some methods that can be used to models and calculate the mineral reserves. One method that can be used is the conventional methods. The conventional method which often used is cross section method, Inverse Distance Square (IDS), and Nearest Point Neighborhood (NNP). Based on the analysis and data processing in mind that the three conventional methods can be used in modeling and calculating nickel laterit reserves. Nickel reserve calculation results in Block A with section method, IDS and NNP for HSOZ is 84,506, 88,567 and 88,583 tons. Estimation results on Block C is 7.135, 6.676 dan 6.677 tons. While estimation result for Block B is calculated with IDS and NNP method is 46.975 dan 46.774 tons.